The Effect of Character Education and Creative Learning on Improving Student Learning Outcomes with Learning Motivation as a Moderating Variable at State Senior High School 2 Tana Toraja - Tria Sampelunak; Muh. Ihsan Said Ahmad; Ika Wisudawaty; Andi Zulitsnayarti Mardani Syam; Ratnah S Ratnah S (Institut Teknologi Pendidikan Indonesia, 2026)
This study aims to analyze the effect of character education and creative learning on improving student learning outcomes with learning motivation as a moderating variable at SMA Negeri 2 Tana Toraja. This study was motivated by low student learning outcomes influenced by the less than optimal implementation of character education, conventional learning, and varying levels of student learning motivation. The study used a quantitative approach with the Structural Equation Modeling method based on Partial Least Square (SEM-PLS). The study sample consisted of 173 students selected using proportionate stratified random sampling. Data were collected through questionnaires and documentation, then analyzed using statistical analysis with a moderation approach to test the relationship between variables. The results showed that character education had a positive and significant effect on student learning outcomes, as well as creative learning, which was proven to be able to significantly improve learning outcomes. Learning motivation also had a positive effect on student learning outcomes. In addition, learning motivation was able to moderate the relationship between character education and creative learning on learning outcomes, so that the influence of both variables was stronger in students with high learning motivation. This study implies that the integration of character education and creative learning supported by high motivation is effective in improving learning outcomes. Therefore, teachers and schools are expected to be able to create a creative, character-based and motivating learning environment in a sustainable manner.